PERFORMANCE AND PEER ASSESSMENT ANALYSIS TOWARDS STUDENTS’ SCIENTIFIC WORK THROUGH STEM-BASED VIRTUAL LABORATORY LEARNING - Ratih Permana Sari; Mauliza Mauliza; R. Ahmad Zaky El Islami (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2020)
This study aimed to analyze the application of performance and peer assessment to students' scientific work through a STEM-based virtual laboratory learning. The research design was used the One Group Pretest-Posttest and One-Shot Case Study. The research was carried out from July to September 2020 at Chemistry Education Department, one of the universities in Indonesia. The research subjects were chemistry education students for the 2018/2019 Academic Year with a purposive sampling technique. The research data was taken from the performance assessment observation sheet given before and after the laboratory practice learning process and the peer assessment questionnaire. The data listed on the observation sheet and questionnaire are then calculated for the percentage. Based on research results, it can be concluded that the implementation of performance and peer assessment of students' scientific work through STEM-based virtual laboratory learning are very competent criteria at 86% and competent at 84%. The results of the paired sample t-test of students' scientific work abilities assessed using the performance assessment have a Sig. (2- tailed) the value below 0.05, which is 0.000, where there is a difference in the average results of initial and final observations using performance assessment through STEM-based virtual laboratory learning. One sample t-test of students' scientific work abilities assessed using performance and peer assessment has Sig. (2- tailed) values of 0.011 and 0.002 indicate that the mean score of students’ scientific work is 75.